Characterization of resistance profile of Mycobacterium tuberculosis isolates from patients with tuberculosis in Beira, Sofala - Mozambique - Namburete, Evangelina Inácio; Lisboa, Miguelhete; Tivane, Inês; Harrison, Lee; Bollela, Valdes Roberto (Medicina (Ribeirao Preto), 2016)
Objective: To analyze the resistance profile of Mycobacterium tuberculosis isolates from patients with tuberculosis in Beira, Sofala, Mozambique. Method: Descriptive cross-sectional study that analyzed secondary data from patients who had positive culture for M. tuberculosis on MGIT960-BACTECTM. For each patient, demographic data, information of Human Immunodeficiency Virus (HIV) serology, rapid molecular test - GeneXpertα-Cepheid result and first line drug susceptibility test (DST) were reviewed . All tests were performed in the Referral Laboratory of Tuberculosis in Beira, from January 2014 to March 2015. Findings: Totally of 87 isolates from Sofala province, Mozambique were analyzed. Of these, 33/87 (37.9%) isolates had any anti-TB drug resistance detected while in 54/87 (62.1%) the drug resistance was not detected. Among the 33 isolates with drug resistance: 18/33 (54,7%) were multidrug-resistant (MDR), 11/33 (33,3%) were Isoniazid (INH) mono-resistant, 2/33 (6%) Rifampicin (RIF) mono-resistant and 2/33 (6%) were Etambutol mono-resistant. Of the total isolates with resistance to INH, 5/11 (42%) were additionally resistance to streptomycin (Sm). Of the 49 patients with HIV serology known, 30 (61,2%) were confirmed HIV positive. The HIV infection was two times more frequent among patients with drug resistant compared to those without drug resistance. All isolates resistant to INH and RIF (MDR) had previous history of tuberculosis treatment. Conclusion: There is high proportion of co-infection TB/HIV among patients with any drug resistant TB MDR or monoresistance . We also observed high frequency of monoresistance to isoniazid and association of drug resistance between isoniazid and streptomycin